Impactos do manejo do bacuri (Platonia insignis Mart.) na estrutura da vegetação de cerrado stricto sensu na reserva extrativista Chapada Limpa, Chapadinha/MA - Vivian do Carmo Loch (2013)
The Extractive Reserve (Resex) Chapada Limpa was established in 2007 in order to preserve the cerrado biodiversity and to protect traditional populations that have in the extraction of bacuri one of their main sources of income. Knowledge on the composition and structure of tree communities within the cerrado stricto sensu areas of the Extractive Reserve (Resex) Chapada Limpa is incipient and it is necessary to make better use the managed forest to provide expansion of opportunities for income generation for the extractivist people. This study aimed phytosociologic characterization of the areas where Platonia insignis Mart. Occurs. Additionally, to understand how communities interact with environmental resources in the place they live and how their management actions affect the Reserve conservation. To delimit the sample we identified and georeferenced bacuri extraction areas, strategically divided into four territories: Juçaral, Chapada Limpa I, Chapada Limpa II and Chapada do Riachão. In the phytosociological study, the method used took plots of 20 x 50 m as the sample unit, randomly distributed, with 5 plots in each of the 4 areas, totaling 2 ha inventoried. All living plants with base diameter greater than 5 cm (D > 5 cm) were measured. Then, we calculated the phytosociological parameters – density, frequency, dominance and importance value. The diameters and heights of trees of each sampled area were divided into classes. The diversity index was calculated by the Shannon-Wiener measure (H’). Were listed in the areas studied a total of 1090 living individuals in 52 species distributed among 21 families. Regarding Percentage of Importance (PI), stand out the families Vochysiaceae (30.59%), Fabaceae (24.47%), Clusiaceae (11.01%), Malpighiaceae (9.60%). The study identified the species Platonia insignis, Qualea parviflora Mart., Vatairea macrocarpa (Benth.) Ducke and Stryphnodendron coriaceum Benth. as the most important from the ecological aspect. In the second part of the research, ethnobotanical investigations were carried out. We defined that only the communities of the Reserve where there is bacuri (Chapada Limpa I, Chapada Limpa II and Juçaral) would be studied. All the extractivist workers from these communities were interviewed using the snowball technique, totaling 34 interviewees. The questions were related to the socioeconomic conditions, resources use and bacuri management. We used informal conversations, semi-structured interviews and participant observation. We recorded 55 species cited as useful by families and most references were about bacuri, janaúba (Himatanthus drasticus), babaçu (Attalea speciosa), mangaba-brava (Lafoensia pacari), murici (Byrsonima sp), buriti (Mauritia flexuosa), candeia (Plathymenia reticulata), juçara (Euterpe oleracea) e sucupira (Bowdichia virgilioides). Other species were highlighted by the economic potential because of its abundance in the study areas (barbatimão (Stryphnodendron coriaceum) and janaúba). Bacuri, despite being offered only during four months of the year, is the most economically important species for extractivist families. Half of the interviewees claimed to collect among 51 to 100 fruits per day, resulting in a monthly increase of R$ 750,00 in the family income. Bacuri is a very important species to the residents of Resex Chapada Limpa and this is reflected in the way they manage the areas. We suggest that the practice of collecting receive special care and we recommend the development of strategies for conservation and sustainable harvesting